Budd-Chiari Syndrome with Multiple Thrombi due to a Familial Arg42Ser Mutation in the Protein C Gene - Jun Muratsu; Atsuyuki Morishima; Kazuhiro Mizoguchi; Keiji Ataka; Hiroshi Yamamoto; Xinping Fan; Toshiyuki Miyata; Katsuhiko Sakaguchi (Case Reports in Medicine)
A 34-year-old Japanese woman was admitted to our hospital complaining of developing bilateral pedal edema. Imaging studies led to a diagnosis of Budd-Chiari syndrome combined with internal jugular vein thrombus. We investigated the cause of thrombosis and found that the anticoagulant activity of protein C was decreased. Genetic analysis showed the presence of a c.125C>A (Arg42Ser) substitution in the protein C gene (PROC) of the proband, which generates an Arg42Ser mutation that replaces the scissile bond Arg42-Ala43 normally cleaved by a furin-like processing protease. Her father and younger brother also carried this mutation, although they had no evidence of thrombosis.